AN ANALYSIS OF CODE-SWITCHING BY EFL LECTURERS IN TOURISM CLASSROOM SETTING - Satria Rusdy Wijaya (Media Bina Ilmiah, 2024)
The use of code-switching by EFL lecturers in tourism classroom activities, particularly the linguistic features, functions, and motivation to use it in the teaching-learning process, is a pressing subject to be addressed in this study. This study used a descriptive qualitative technique for its research design. This approach focuses on natural occurrences and provides a methodical, factual, and precise explanation of the issue, particularly when EFL lecturers employ code-switching in the classroom. Based on the findings in the previous chapter, the writer can conclude as follows: There are 182 utterances of codeswitching found on lecturer’s utterances. Of the 182 utterances switched 77 utterances are in words, 16 are in phrases, 19 are in clauses, and 70 are in sentences. The mostly switched element is words with 77 utterances or 42 % of total of the whole utterances, followed by sentences 70 utterances (38%), 19 times or 11% in the form of clauses and 16 or 9% in the form of phrases, Out of the 77 switched words or language elements, 9 utterances are nouns, 7 are verbs or 9%, 12 are adjectives or 16%, 4 times are adverbs or 4%. It is also found switching elements in preposition 6 times and interjection 39 times for its occurrence. The most frequency is switching element in adjectives with 12% in total, followed by nouns (9%), verbs (7%), and preposition (6%) and There are nine reasons to codeswitch found in this study. The most frequently is interjection (83%) with 43 times of its occurrences, followed by expressing self (6%), soften or strengthen request or command (4%), intention of clarifying, repetition, express solidarity, and talking about particular topic are 2% for each. Interjection is the most frequently found as the reason to codeswitch, it is because the lecturers may be interfered by their first language that is Bahasa Indonesia. The lecturers cannot escape the influence of their native language and that makes lecturers feel free and comfortable to express their emotional feelings, and ideas